Urine Sample-Derived Cerebral Organoids Suitable for Studying Neurodevelopment and Pharmacological Responses - Lin, Victor J. T.; Hu, Jiangnan; Zolekar, Ashwini; Yan, Liang-Jun; Wang, Yu-Chieh (Frontiers in Cell and Developmental Biology, 2020)
Cerebral organoids (COs) developed from human induced pluripotent stem cells (hiPSCs) have been noticed for their potential in research and clinical applications. While skin fibroblast-derived hiPSCs are proficient at forming COs, the cellular and molecular features of COs developed using hiPSCs generated from other somatic cells have not been systematically examined. Urinary epithelial cells (UECs) isolated from human urine samples are somatic cells that can be noninvasively collected from most individuals. In this work, we streamlined the production of COs using hiPSCs reprogrammed from urine sample–derived UECs. UEC-derived hiPSC‒developed COs presented a robust capacity for neurogenesis and astrogliogenesis. Although UEC-derived hiPSCs required specific protocol optimization to properly form COs, the cellular and transcriptomic features of COs developed from UEC-derived hiPSCs were comparable to those of COs developed from embryonic stem cells. UEC-derived hiPSC‒developed COs that were initially committed to forebrain development showed cellular plasticity to transition between prosencephalic and rhombencephalic fates in vitro and in vivo, indicating their potential to develop into the cell components of various brain regions. The opposite regulation of AKT activity and neural differentiation was found in these COs treated with AKT and PTEN inhibitors. Overall, our data reveal the suitability, advantage and possible limitations of human urine sample‒derived COs for studying neurodevelopment and pharmacological responses.